2022
DOI: 10.1039/d1fo03308e
|View full text |Cite
|
Sign up to set email alerts
|

Rice bran protein oxidation induced by rancidity alters the gut microbiota and intestinal permeability in mice

Abstract: Oxidized RBP induced by rice bran rancidity changes the gut microbiota profile, slightly affects the production of SCFAs, and improves the intestinal barrier by upregulating the expression of tight junction proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Li et al (2016) found that oxidized tyrosine products were mainly composed of dityrosine, 3-nitrotyrosine, and tyrosine, which had been widely identified in milk powder and processed meat food, and had been associated with physiological processes. A 24-week feeding of oxidized tyrosine (2, 4, 8 g/kg diet) induced the antioxidant system impairment, liver and kidney dysfunction, and fibrosis in the liver via the MAPK/TGF-𝛽1 signaling pathway and in the kidneys via the JNK/p38 signaling pathway (Li et al, F I G U R E 1 Dietary protein oxidation induces the damage on body health (Ahmad et al, 2019;Ding et al, 2017c;Li et al, 2016Li et al, , 2017Li et al, , 2022aLu et al, 2020;Ran et al, 2016) on mouse myocardial function. The dityrosine dose was determined according to the amount of reconstituted milk (3% protein content) consumed daily by a 5-kg baby, and the dose of oxidized tyrosine products was equal to dityrosine content (22%) in oxidized tyrosine (Lu et al, 2020).…”
Section: Oxidation Products Of Dietary Proteins and Organ Damagementioning
confidence: 99%
See 4 more Smart Citations
“…Li et al (2016) found that oxidized tyrosine products were mainly composed of dityrosine, 3-nitrotyrosine, and tyrosine, which had been widely identified in milk powder and processed meat food, and had been associated with physiological processes. A 24-week feeding of oxidized tyrosine (2, 4, 8 g/kg diet) induced the antioxidant system impairment, liver and kidney dysfunction, and fibrosis in the liver via the MAPK/TGF-𝛽1 signaling pathway and in the kidneys via the JNK/p38 signaling pathway (Li et al, F I G U R E 1 Dietary protein oxidation induces the damage on body health (Ahmad et al, 2019;Ding et al, 2017c;Li et al, 2016Li et al, , 2017Li et al, , 2022aLu et al, 2020;Ran et al, 2016) on mouse myocardial function. The dityrosine dose was determined according to the amount of reconstituted milk (3% protein content) consumed daily by a 5-kg baby, and the dose of oxidized tyrosine products was equal to dityrosine content (22%) in oxidized tyrosine (Lu et al, 2020).…”
Section: Oxidation Products Of Dietary Proteins and Organ Damagementioning
confidence: 99%
“…The influence of oxidized dietary proteins on gut microbiota has been presented in Table 3. Li et al (2022a) prepared oxidized rice bran protein by storing rice bran for different periods for a 12-week gavage experiment. Compared with raw rice bran protein (isolated from rice bran stored for 0 days), oxidized rice bran protein (isolated from rice bran stored for 3 and 10 days) significantly changed the number of gut microbiota, as reflected by the richness indices (Chao1 and Observed operational taxonomic units (OTUs)) of gut microbiota in the colon.…”
Section: Dietary Protein Oxidation and Gut Microbiotamentioning
confidence: 99%
See 3 more Smart Citations